Effect of Alkalized Pineapple Leaf Fiber Direction Variations on Tensile Strength and Bending of Polyester Matrix Composites - Gugun Gundara; Agung Setia Nurzein; Acep Wagiman; Asep Romi Ramadhan (Formosa Journal of Sustainable Research, 2023)
Pineapple plant is a plant that is often found throughout Indonesia, so that the production of pineapple is very abundant. Pineapple leaf fiber which consists of about 70-80% cellulose provides high modulus and strength properties, this causes pineapple leaves to be used as an efficient reinforcement of natural fiber composites. In this study, the material used was pineapple leaf fiber which had been alkalized in the direction of 0°, 45°, 90° with a volume fraction of 50% with alkalization (NaOH) treatment for 1 hour and 2 hours, without treatment. This study used polyester resin as the matrix with the hand lay up method. The test results for the pineapple leaf fiber composites which have been alkalized with variations in direction 0°, 45°, 90° with a volume fraction of 50%. And the highest value in the tensile test with treatment is in the 0° direction with a value of 5.883 MPa and an average value of 4.306 MPa with 2 hours of immersion and for the bending test the highest value is in the 0° direction with a value of 3.922 MPa and an average value of 3.276 MPa with 2 hours immersion. The 0° fiber direction has the best stress because the fiber direction is directly proportional to the static load given to the tensile and bending testing machine. Conversely, the direction of 90° is inversely proportional because the direction is not the same as the static load that is given